Factors Impacting Student Satisfaction in Online Design Education: A Case Study of a Public University in Nanchang, China - Li, Shuyao (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: The study was designed to explore the factors influencing the online education satisfaction of undergraduate students at Art College of Nanchang University, China. Four variables of competence, responsiveness, empathy, and patience were investigated for their effects on the dependent variable of student satisfaction. Research design, data and methodology: The item-objective consistency index (IOC) was used to measure the validity of the survey questionnaire, and Cronbach’s alpha was used for the pilot test (n=90). The 90 valid student questionnaires were analyzed by multiple linear regression to analyze the significant relationship between variables. A 12-week Intervention Design Implementation (IDI) was conducted with 30 undergraduate students (n=30) and three faculty representatives who had experienced online education. Then, Pre- and Post-IDI quantitative results were compared using paired-sample t-tests. Results: The study found that teachers’ competence, responsiveness, empathy, and patience significantly impacted students’ online learning satisfaction. The interviews revealed that post-intervention students widely reported that the teachers’ teaching content was more appealing and practical, which enhanced students’ trust in the teachers and their sense of security in learning. This boosted students’ emotional engagement and satisfaction. Conclusions: The results indicate that systematic enhancement of teachers’ competence could significantly improve students’ online learning experience, revealing the importance of the balance between technological empowerment and humanistic care for improving education quality.